KEMAH BUDAYA Di Desa Kertayasa - Firmansyah, Fachru Nur Fahmi; Mulyana, Deni Adi; Fadhlurrohman, M. Arif; I.P, A. Fadhilah; Reihansyah, Luthfi; Maolana, Rizki; Nurrohim, Fajar Dzikri; Kilten N, Karin (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
Pangandaran has a fairly high focus on development that supports tourism. This development includes physical development, human resources, and innovative tourism development based on local wisdom. With the slogan